Review of Law Number 11 of 2020 on Job Creation: Constitutionality Test Based on Constitutional Court Decision Number 91/PUU-XVIII/2020 - Burhanuddin, Ahmad; Priyana, Yana (Westscience Press, 2025)
This study conducts a normative legal analysis of Law Number 11 of 2020 on Job Creation (commonly referred to as the Omnibus Law), focusing on its constitutionality as assessed in Constitutional Court Decision Number 91/PUU-XVIII/2020. The research examines the legal and procedural foundations of the law's formation and evaluates whether it adhered to the standards set by the 1945 Constitution of the Republic of Indonesia. The Constitutional Court declared the law